Fully-ambient-processed mesoscopic semitransparent perovskite solar cells by islands-structure-MAPbI3-xClx-NiO composite and Al2O3/NiO interface engineering. (July 2018) - Wang, Yousheng; Mahmoudi, Tahmineh; Yang, Hwa-Young; Bhat, Kiesar Sideeq; Yoo, Jin-Young; Hahn, Yoon-Bong
Abstract: Perovskite solar cells (PSCs) because of low-cost fabrication and high performance have shown superb potential for the next-generation photovoltaic application. For the potential applications of photovoltaic technologies, semitransparent PSCs are also highly attractive and of commercial interest to develop building- and tandem-integrated solar cells. Here, we present fully-ambient-processed stable and mesoscopic semitransparent PSCs by non-continuous islands-structure-CH3 NH3 PbI3-x Clx -NiO nanoparticles (MAPbI3-x Clx -NiO NPs) composite and interface engineering by inserting Al2 O3 /NiO between TiO2 and MAPbI3-x Clx -NiO composite layers in a device configuration of FTO/c-TiO2 /mp-TiO2 /Al2 O3 /NiO/islands-structure-MAPbI3-x Clx -NiO /spiro-OMeTAD/Au. Except for the islands-structure-MAPbI3-x Clx -NiO capping layer, a uniform and thicker and transparent TiO2 /Al2 O3 /NiO/MAPbI3-x Clx composite layer is formed, which can effectively reduce photocurrent density loss and interface recombination. Interestingly, the optimized semitransparent PSCs showed hysteresis-free performance. The average visible transmittance (AVT) of MAPbI3-x Clx -NiO NPs composite film was ranged from 18% to 56% and the corresponding device PCE changed from 17.51% to 12.47%. The PSCs without encapsulation showed an excellent air stability over 270 days with retaining 98% of its original V oc, 96% of J sc, 97% of FF and 93% of PCE under ambient condition (25–30 ℃ and 45–50% humidity). Finally, we achieved semitransparent device of PCE = 10.06%, corresponding to AVT = 27%. Graphical abstract: Conceptual illustration and performance of Mesoscopic Semitransparent Perovskite Solar Cells by Islands-structure-MAPbI3-x Clx -NiO Composite and Al2 O3 /NiO Interface Engineering.fx1 Highlights: Semitransparent PSCs based on islands-structure-MAPbI3-x Clx -NiO composite and Al2 O3 /NiO interfacial engineering. Reduction of photocurrent loss and interface recombination by thick, semitransparent TiO2 /Al2 O3 /NiO/MAPbI3-x Clx . Real semitransparent devices with PCE =10.06% and average visible transmittance of 27%. Excellent air-stability over 270 days with retaining more than 93% of performance parameters under ambient condition.